Preoperative Hand Decontamination in Ophthalmic Surgery: A Comparison of the Removal of Bacteria from Surgeons' Hands by Routine Antimicrobial Scrub versus an Alcoholic Hand Rub. (2nd September 2017) - Forer, Yaara; Block, Colin; Frenkel, Shahar
ABSTRACT: Purpose : The goal of this experiment was to evaluate and compare the antimicrobial efficacy of routine preoperative hand washing using commercial medicated sponge brushes versus an alcoholic hand rub, by comparing bacterial growth on ophthalmic surgeons' hands after application of each of these methods. Methods : Twenty ophthalmic surgeons were recruited at the Hadassah-Hebrew University Medical Center in Jerusalem, Israel. Samples were collected twice from the hands of each surgeon after hand decontamination using two different protocols during routine surgical practice. The routine preparation consisted of a 3-minute surgical scrub using commercial brush-sponges incorporating either 4% chlorhexidine gluconate (CHG) or 1% povidone–iodine (PVP-I) formulations with detergent, followed by drying the hands with a sterile towel, while the 70% ethanol solution was applied for 60-seconds and allowed to air dry. Half of the group was randomly assigned to provide samples first after the routine method and the alcoholic solution a week later, and the other half of the group was sampled in the reverse order. Viable counts of bacteria were evaluated using a modified glove juice method. Bacterial colonies were enumerated after incubation for 24 hours and expressed as colony forming units (CFU)/mL for each pair of hands. Results : Geometric mean counts were 1310 and 39 CFU/mL, in the routine and alcohol rub groups, respectively, representing a mean log10 reduction in 1.53. The difference between the paired bacterial counts for the routine versus the alcohol rub was statistically significant ( p < 0.0001). There was no statistically significant difference between log10 reductions for CHG and PVP-I ( p = 0.97). Conclusions : This study provides evidence that an alcohol rub protocol is more effective in reducing bacterial counts on hands than routine surgical hand preparation with PVP-I and CHG in a population of practicing ophthalmic surgeons in the operative clinical setting. Thus, it provides a safe alternative as a preoperative hand disinfection method.